E-VAC therapy as treatment of complications in gastrointestinal surgery in a gastroenterology reference center in Colombia: Case series - Fuentes, Carlos Fernando (2023)
Gastrointestinal postoperative anastomotic leaks and fistulas occur frequently and many are managed surgically; however, endoscopic interventions have shown to improve healing outcomes and length of hospital stay. The experience of vacuum-assisted closure therapy (E-VAC) is described, in complications such as fistulas and postoperative anastomotic leaks, in a gastrointestinal reference center in Colombia. A case series study was carried out in patients with anastomotic leaks and fistulas at different levels of the digestive tract, treated by E-VAC, by the Gastroenterology Service in Colombia, during a period from February 2019 to November 2021. Sociodemographic, clinical and surgical variables were described. 6 cases are described, 4 from lower digestive tract and 2 from upper digestive tract. 83% were men; the mean age was 51.8 years (+/-17.5). The indication for E-VAC was colorectal anastomotic fistula in 66%; the most frequent anatomical location was near the anal region (66%), less frequently at the level of the cardia (16%) and esophagus (16%). The size of the defect was described between 20 and 80% in patients undergoing E-VAC therapy, with an average hospitalization length of stay of 22.5 days, with an average number of exchanges of seven per patient. Anastomotic leaks and fistulas are potentially fatal complications in gastrointestinal surgery. E-VAC therapy has shown to be effective and safe, promoting defect closure and drainage of collections present, also decreasing the length of hospital stay.